Calculating the Notional Learning Hours (NLH) for Final Year Medical Students in a Clinical Surgery Clerkship Course - Gamal EHA EL Shallaly; Nausheen Saeed; Sathyanarayan Rao (Sudan Journal of Medical Sciences)
Abstract Background: The main objective of this study is to design a method to calculate the notional learning hours (NLH) of final-year medical students doing a surgical clerkship course, as current methods are based only on assumptions. Secondary objectives include derivation of the Oman Qualification Framework (OQF) credits and setting a benchmark of NLH calculation in clinical courses. Methods: This is an observational cross-sectional study which uses quantitative methods to estimate students' NLH. A questionnaire was designed and filled in by final-year medical students at the end of their surgical rotation. Ethical clearance was obtained. Data were uploaded and analyzed using the SPSS 25. The NLH was then calculated and mapped onto the OQF template. Results: Ninety-seven students participated in the study. Students spent an average of 1.20 hrs/day studying for their clinical sessions and 2.86/day studying for their theory sessions. The mean weekend hours of study on Friday and Saturday were 3.1 and 3.2 hrs, respectively. The average preparation for the end rotation and the final graduating (MD) exams were 9.7 and 10.4 hrs, respectively. We calculated the NLH of our students by adding the above data to the contact teaching hours from our course timetable. We compared our results with medical schools worldwide. Conclusion: TheNLH of our surgical clerkship students was calculated and subsequently the OQF credits were derived. Our method is based on real-life students' study hours and not on unproven assumptions. It could be used as a guide by other clinical clerkship courses.